2008
DOI: 10.5194/gh-63-26-2008
|View full text |Cite
|
Sign up to set email alerts
|

Denudation and landslides in coastal mountain watersheds : 10,000 years of erosion

Abstract: Abstract. A conceptual model of landslide-induced denudation for coastal mountain watersheds spanning 10,000 years of environmental change is presented. The model uses a constructed paleo-climate based on vegetation records and an established relationship between landslide frequencies and precipitation. Landslide frequencies are determined for the early warm dry Holocene, the warm wet middle Holocene and modern climates. Average landslide rates vary between 0.005 landslides·y-1·km-2 and 0.008 landslides·y-1·km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the Pacific Northwest, the absence of mature timber appears to increase not only the frequency of debris flow activity (Schwab, 1983;Rood, 1984;Jakob, 2000;Guthrie, 2002Guthrie, , 2005Guthrie and Brown, 2008), but also the magnitude and travel distance of individual events (Robison et al, 1999;Bunn and Montgomery, 2000;Lancaster et al, 2003;May and Gresswell, 2003;Miller and Burnett, 2008;among others). Landslide research from the Coast Range of Oregon demonstrates several ways in which forests can influence debris flow runout: Debris flows have lower mean runout lengths and shorter depositional zones in mature forests (Robison, et al, 1999;May and Gresswell, 2003;Miller and Burnett, 2008), while landslides in younger stands (< 9 years) have increased volumes of erosion compared to regenerating stands (9-100 years) (Robison et al, 1999).…”
Section: The Impact Of Forests Roads and Benches On Landslide Runoutmentioning
confidence: 96%
See 2 more Smart Citations
“…In the Pacific Northwest, the absence of mature timber appears to increase not only the frequency of debris flow activity (Schwab, 1983;Rood, 1984;Jakob, 2000;Guthrie, 2002Guthrie, , 2005Guthrie and Brown, 2008), but also the magnitude and travel distance of individual events (Robison et al, 1999;Bunn and Montgomery, 2000;Lancaster et al, 2003;May and Gresswell, 2003;Miller and Burnett, 2008;among others). Landslide research from the Coast Range of Oregon demonstrates several ways in which forests can influence debris flow runout: Debris flows have lower mean runout lengths and shorter depositional zones in mature forests (Robison, et al, 1999;May and Gresswell, 2003;Miller and Burnett, 2008), while landslides in younger stands (< 9 years) have increased volumes of erosion compared to regenerating stands (9-100 years) (Robison et al, 1999).…”
Section: The Impact Of Forests Roads and Benches On Landslide Runoutmentioning
confidence: 96%
“…Forestry has been the primary resource-based industry in BC over the last century, exploiting~400 000 km 2 of merchantable timber. Unfortunately, forest operations are not without impact; and the occurrence of landslides, naturally common on BC's steep terrain, increased by about an order of magnitude in the last several decades (Schwab, 1983;Jakob, 2000;Guthrie, 2002;Guthrie and Brown, 2008). Guthrie and Brown (2008) reported that human-induced landslides have approximately doubled landscape erosion over the next highest millennia (the Holocene).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…P (F ) derived from simulations exhibits low probabilities where slopes are moderate and cohesion is high (e.g., forest). Highly unstable areas largely correspond to steep barren landscape (13 % of the model domain) mostly located below retreating alpine glaciers, with steep glacial landforms, transitioning from glacier to colluvial processes (similar to Guthrie and Brown, 2008;Tarolli et al, 2008;Legg et al, 2014) (Fig. 9).…”
Section: Probability Of Failurementioning
confidence: 99%
“…P (F ) derived from simulations exhibits low probabilities where slopes are moderate and cohesion is high (e.g., forest). Highly unstable areas largely correspond to steep barren landscape (13 % of the model domain) mostly located below retreating alpine glaciers, with steep glacial landforms, transitioning from glacier to colluvial processes (similar to Guthrie and Brown, 2008;Tarolli et al, 2008;Legg et al, 2014) (Fig. 9).…”
Section: Probability Of Failurementioning
confidence: 99%